A Granular View of the Australian Business Cycle. Issue 311 (5th September 2019) - Miranda‐Pinto, Jorge; Shen, Yuanting
Abstract : We provide evidence supporting the hypothesis that idiosyncratic firm‐level shocks are important drivers of the Australian business cycle ( granular hypothesis ). We first document that the distribution of firm size in Australia is substantially asymmetric and follows a power‐law distribution with a long right tail. We then show that labour productivity shocks to the largest non‐financial firms in Australia account for about 20–40 per cent of the variation in Australian GDP growth over the period 2000–18. Besides energy sector firms, firms in the construction, transportation and consumer services sectors appear to be relevant drivers of GDP growth.